Reservoir characteristics and enrichment features of the low-permeability to tight transition zone in the Jishan Sandstone, Shang 541 area - Chao, Huang; Jianhui, Zeng; Yuanyuan, Zhang (Frontiers in Earth Science, 2025)
The physical property boundary between conventional low-permeability and unconventional tight sandstone oil reservoirs is generally defined at a permeability of 1 × 10−3 μm2. Understanding the reservoir characteristics and hydrocarbon enrichment patterns within this transitional zone is of significant importance for the comprehensive evaluation of the whole petroleum system. This study investigates the petrology, physical properties, and microscopic pore-throat structures of this transition zone using core analysis data from four cored wells of the Jishan Sandstone in the Shang 541 area, located in the Huimin Sag of the Jiyang Depression. Furthermore, it analyzes the oil-bearing characteristics and controlling factors by integrating drilling results from 13 wells, core water‐drop tests, and core oil saturation measurements. The reservoirs in the study area are composed of lithic arkose, with intergranular dissolution pores and primary intergranular pores as the dominant storage space types. Petrophysical properties are strongly influenced by burial depth, causing the reservoir to transition from a conventional low-permeability system in the west to a tight system in the east as depth increases. The transitional zone reservoirs exhibit an average pore-throat radius of 0.2–0.3 μm, and a strong positive correlation is observed between permeability and mean pore-throat radius. Areal hydrocarbon distribution is controlled by two primary factors. First, as reservoir quality improves towards shallower depths, the capillary self-sealing effect weakens, leading to a decrease in oil saturation and a shift from oil layers to oil-water and water layers. Second, under a “source-fault-reservoir” lateral contact charging model, enrichment is greatest in proximity to faults. Far from the fault conduit, hydrocarbon expulsion pressure diminishes, preventing effective charge and resulting in water-bearing reservoirs. This research significantly enhances the understanding of enrichment patterns in conventional-unconventional transitional reservoirs and provides valuable guidance for exploration and development in the Jiyang Depression.